Theological, Ecological, and Humanist Educational Values in the Tafsir of Surah Al-falaq: Hamka's Perspective - Wendi Parwanto (EL-TARBAWI, 2022)
Despite research on Surah Al-Falaq and the Hamka's educational values ​​ have been carried out by several researchers, a study integrating educational values ​​in Surah Al-Falaq from the Hamka perspective has never been studied. This study examines the theological, ecological, and humanist values in Surah Al-Falaq from Hamka's perspective. Through library research, a descriptive-analytical method was in this study. The formal object of this research is Tafsir Al-Azhar, while the material object is Surah al-Falaq. Some conclusions were drawn from this study. First, the value of theological education in Surah A-Falaq includes 1) Allah as the best place to ask for help and protection; 2) Obedience and tawhid to Allah minimize evil in the human's heart. Second, the value of ecological education includes 1) Being grateful to God for His favors by loving nature; 2) Fostering a conservative and preventive attitude towards nature. Third, the value of humanist education includes 1) Preventing dangers in life; 2) Cultivating social harmony to minimize social inequality.